Salinity stress-induced phosphorylation of INDETERMINATE-DOMAIN 4 (IDD4) by MPK6 regulates plant growth adaptation in Arabidopsis - Rawat, Anamika; Völz, Ronny; Sheikh, Arsheed; Mariappan, Kiruthiga G.; Kim, Soon-Kap; Rayapuram, Naganand; Alwutayd, Khairiah M.; Alidrissi, Louai K.; Benhamed, Moussa; Blilou, Ikram; Hirt, Heribert (Frontiers in Plant Science, 2023)
The INDETERMINATE DOMAIN (IDD) family belongs to a group of plant-specific transcription factors that coordinates plant growth/development and immunity. However, the function and mode of action of IDDs during abiotic stress, such as salt, are poorly understood. We used idd4 transgenic lines and screened them under salt stress to find the involvement of IDD4 in salinity stress tolerance The genetic disruption of IDD4 increases salt-tolerance, characterized by sustained plant growth, improved Na+/K+ ratio, and decreased stomatal density/aperture. Yet, IDD4 overexpressing plants were hypersensitive to salt-stress with an increase in stomatal density and pore size. Transcriptomic and ChIP-seq analyses revealed that IDD4 directly controls an important set of genes involved in abiotic stress/salinity responses. Interestingly, using anti-IDD4-pS73 antibody we discovered that IDD4 is specifically phosphorylated at serine-73 by MPK6 in vivo under salinity stress. Analysis of plants expressing the phospho-dead and phospho-mimicking IDD4 versions proved that phosphorylation of IDD4 plays a crucial role in plant transcriptional reprogramming of salt-stress genes. Altogether, we show that salt stress adaption involves MPK6 phosphorylation of IDD4 thereby regulating IDD4 DNA-binding and expression of target genes.